RETRACTED: The Effects of Physical Exercise on Cognition: How Heart Rate Variability Can Predict Cognitive Performances - Sannino, Giovanna; De Falco, Ivanoe; De Pietro, Giuseppe; Stranges, Saverio (Frontiers in Human Neuroscience, 2020)
Objectives: Investigate and identify the relationship between physical exercise and cognitive performance measured by using a number of different cognitive tests taken from Cambridge Brain Science (CBS). Methods: Thirty subjects, divided into two groups (aerobic and effort), undergo twelve cognitive tests from CBS. A comparison between the pre- and post-exercise results in terms of cognitive performance differences is carried out. Regression analysis between Heart Rate Variability (HRV) features and CBS tests results is performed. Results: In most CBS tests there is an improvement, or at least a confirmation, of the subject’s cognitive ability, for both groups. Reasoning (80-100%), concentration (80-87%), and planning tests (93-100%) seem to undergo important positive changes. The regression analysis, performed by using a set of different algorithms, has demonstrated that it is possible, by monitoring the HRV during the exercise, to predict to some extent the cognitive performance, i.e. the CBS tests results. The best performing regression algorithms are Simple Linear (Quade Test - aerobic group: 2.098, effort group: 3.350, both groups: 2.747) and REPTree (Quade Test - aerobic group: 2.955, effort group: 3.315, both groups: 3.121). The statistical analysis has proved that physical activity is statistically useful for the subjects in improving their cognitive performance. Conclusions: This study has numerically appraised the improvement, the conservation, or the worsening on different aspects of cognition. The found mathematical relationship between physical exercise and cognitive performance suggests that it is possible to predict the beneficial effect of various exercises on executive and attentive control.